Mechanisms of Neuroprotection by Quercetin: Counteracting Oxidative Stress and More. (24th January 2016) - Costa, Lucio G.; Garrick, Jacqueline M.; Roquè, Pamela J.; Pellacani, Claudia
Abstract : Increasing interest has recently focused on determining whether several natural compounds, collectively referred to as nutraceuticals, may exert neuroprotective actions in the developing, adult, and aging nervous system. Quercetin, a polyphenol widely present in nature, has received the most attention in this regard. Several studies in vitro, in experimental animals and in humans, have provided supportive evidence for neuroprotective effects of quercetin, either against neurotoxic chemicals or in various models of neuronal injury and neurodegenerative diseases. The exact mechanisms of such protective effects remain elusive, though many hypotheses have been formulated. In addition to a possible direct antioxidant effect, quercetin may also act by stimulating cellular defenses against oxidative stress. Two such pathways include the induction of Nrf2-ARE and induction of the antioxidant/anti-inflammatory enzyme paraoxonase 2 (PON2). In addition, quercetin has been shown to activate sirtuins (SIRT1), to induce autophagy, and to act as a phytoestrogen, all mechanisms by which quercetin may provide its neuroprotection.